Exploration of the Utilization of Interactive Media in Enhancing Islamic Religious Education Learning - Nurul Sapika; Elmaya Lisa; Salwa Nabila; Hasrian Rudi Setiawan (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to explore the utilization of interactive learning media in enhancing the quality of Islamic Religious Education (IRE) learning. The background of this research is based on the importance of learning media innovation in addressing the challenges of education in the digital era, which requires active student engagement. This research employs a qualitative approach with a descriptive study design. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the use of interactive media significantly enhances students’ learning interest, active participation, and understanding of Islamic Religious Education materials. Furthermore, interactive media provides a more engaging and contextual learning experience. However, several challenges were identified, including limited facilities and teachers’ technological competencies. Therefore, continuous training and institutional support are necessary to optimize the use of interactive media in Islamic Religious Education learning.